The economic and business history of occupied Japan: new perspectives - French, Thomas (Routledge, 2017)
Preface -- Editor's acknowledgments -- Notes on contributors -- Introduction / Thomas French -- Planning, reform, and recovery -- Japanese agency and business reform in occupied Japan : the Holding Company Liquidation Commission and Zaibatsu dissolution / Steven J. Ericson -- Japan's postwar social metabolic crisis / Mark Metzler -- The role of the frontier : GHQ/SCAP economic policies and Hokkaido / Juha Saunavaara -- Industries under occupation -- An empire reborn : the Japanese fishing industry during the occupation / William M. Tsutsui -- Fiats and jeeps : the occupation, jeeps, and the postwar automotive industry -- The Japanese cotton spinning industry and economic recovery under SCAP / Takahiro Ohata -- Socioeconomic changes in the occupation era -- The economic reintegration of former colonial residents in postwar Japan / Steven Ivings -- Good wife, wise mother and Americanised consumer : the forced social democratisation of the private sphere in occupied Japan / Zsombor Rajkai -- Index.
Keywords: Japan -- Economic conditions -- 20th century; Japan -- Social conditions -- 20th century; Electronic books; Aufsatzsammlung; Geschichte 1945-1952; Industrie; Wirtschaftliche Lage; Besetzung; Japan